Alcohol drinking and overall and cause-specific mortality in China: nationally representative prospective study of 220 000 men with 15 years of follow-up - Yang, L; Zhou, M; Sherliker, P; Cai, Y; Peto, R; Wang, L; Millwood, I; Smith, M; Hu, Y; Yang, G; Chen, Z (Oxford University Press, 2012)
Background Regular alcohol drinking contributes both favourably and adversely to health in the Western populations, but its effects on overall and cause-specific mortality in China are still poorly understood.